Pro SharePoint 2007 Development Techniques - Bruggeman, Margriet (Apress, 2012)
We have been working with SharePoint technology since the beta release of SharePoint Portal Server 2001 and have seen the product evolve to SharePoint 2007. The sheer number of new features added to this product line is huge, and we are pleased to note how popular this product has become, since we love working with it. You should read this book if you want to expand your knowledge about developing solutions for both Windows SharePoint Services 3.0 and Microsoft Office SharePoint Server 2007. A few sections only apply to MOSS 2007, but those have been clearly identified. Unfortunately, nowadays SharePoint is such a big topic that you cannot cover every available topic and still provide in-depth information, so we had to choose which topics to include. Since we have started working with Microsoft Office SharePoint Server 2007, we have noticed time and again that all SharePoint developers seem to share a common interest in four topics: building workflows, improving business intelligence, using InfoPath, and creating interactive web environments using Ajax techniques. Therefore, when we decided to write a new book about Share- Point 2007, it was crystal clear to us that we needed to dedicate a considerable portion to these Big Four topics.